2016
DOI: 10.1186/s13034-016-0131-6
|View full text |Cite
|
Sign up to set email alerts
|

Mental health problems in male young offenders in custodial versus community based-programs: implications for juvenile justice interventions

Abstract: BackgroundYoung offenders are known to be a population with high prevalence of mental health disorders. In most cases, these disorders are neither identified nor treated properly, with the majority of them being chronic and difficult to treat. In many countries, the prevalence rates of psychopathology in male young offenders are still unknown and no psychotherapeutic interventions are delivered. Therefore, the main goal of the present study was to assess mental health problems in Portuguese male young offender… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
1
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(63 citation statements)
references
References 45 publications
4
52
1
6
Order By: Relevance
“…Overall, there are a lack of comparable studies regarding mental health among youth prisoners. The prevalence of mental health problems in our study is comparable in certain dimensions to those reported in Sweden and Portugal among prisoners of the same age (12,31). Anxiety problems were at the same rate (52%) but antisocial behaviour was 63% in the Swedish study, considerably higher than in our study where the level was around 41%.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Overall, there are a lack of comparable studies regarding mental health among youth prisoners. The prevalence of mental health problems in our study is comparable in certain dimensions to those reported in Sweden and Portugal among prisoners of the same age (12,31). Anxiety problems were at the same rate (52%) but antisocial behaviour was 63% in the Swedish study, considerably higher than in our study where the level was around 41%.…”
Section: Discussionsupporting
confidence: 73%
“…It is known that somatisation in LMIC has a cultural component and has been understood as a way of expressing distress and trauma; as a result, somatic complaints are often reported instead (32). In the Portuguese study, young male offenders between the ages of 14 and 20 revealed a higher prevalence of mental disorders (91.2%) while in our study 46.33% of the respondents had mental health problems (31).…”
Section: Discussioncontrasting
confidence: 50%
“…The high prevalence of the conduct disorder (CD) diagnosis among juvenile detainees is well established in the literature (Abram et al, 2015; Rijo et al, 2016). In addition, psychopathic traits (i.e., grandiose–manipulative [GM], callous–unemotional [CU], and impulsive–Irresponsible [II] traits) are more prevalent in detained youth than in normative youth (Andershed, Kerr, Stattin, & Levander, 2002; Ribeiro da Silva, Salekin, & Rijo, 2019).…”
Section: Theoretical and Research Basis For Treatmentmentioning
confidence: 99%
“…At baseline, Peter was assessed with the Mini-International Neuropsychiatric Interview for Children and Adolescents (MINI-KID; Sheehan et al, 2010; Portuguese Authorized Version by Rijo et al, 2016). This baseline assessment took place 4 months after Peter’s placement in the detention facility.…”
Section: Assessmentmentioning
confidence: 99%
“…In order to emphasize this problem, policymakers should be informed about their national prevalence rates. For this reason, Rijo and colleagues [4] examined the prevalence rates of mental disorders, including personality disorders, in a randomized sample of male juvenile offenders assessed in the Portuguese Juvenile Justice System. In addition, they compared the prevalence rates of juvenile offenders in custodial and community-based programs.…”
Section: Editorialmentioning
confidence: 99%